2018
DOI: 10.1051/0004-6361/201731424
|View full text |Cite
|
Sign up to set email alerts
|

Double plasma resonance instability as a source of solar zebra emission

Abstract: Context. The double plasma resonance (DPR) instability plays a basic role in the generation of solar radio zebras. In the plasma, consisting of the loss-cone type distribution of hot electrons and much denser and colder background plasma, this instability generates the upper-hybrid waves, which are then transformed into the electromagnetic waves and observed as radio zebras. Aims. In the present paper we numerically study the double plasma resonance instability from the point of view of the zebra interpretatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…We found that due to an error in the growth-rate normalization in our previous paper the growth rate in this paper was overestimated 20 times. Considering this correction the maximal growth rate Γ from the present paper agrees to that in the paper by Benáček & Karlický (2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that due to an error in the growth-rate normalization in our previous paper the growth rate in this paper was overestimated 20 times. Considering this correction the maximal growth rate Γ from the present paper agrees to that in the paper by Benáček & Karlický (2018).…”
Section: Discussionsupporting
confidence: 90%
“…We make simulations using a 3D Particle-in-Cell (PIC) relativistic model (Buneman & Storey 1985;Matsumoto & Omura 1993;Karlický & Bárta 2008;Benáček & Karlický 2018) with multi-core Message Passing Interface (MPI) parallelization. Further details can be found in Matsumoto & Omura (1993, p.67-84) and on the link below.…”
Section: Numerical Growth Rates In the Pic Modelmentioning
confidence: 99%
“…Therefore our gyro-harmonic number agrees to that determined by Chen et al (2011). We note that the gyroharmonic number need not be necessarily an integer number; see the paper by Benáček & Karlický (2018). The plasma density and magnetic field in the zebra-stripe source with s 1 = 12.7 are n = 1.97 × 10 10 cm −3 and B = 35.58 G, respectively (Table 1).…”
Section: Zebra-stripe Sources Moving In Fan Of Magnetic Field Linessupporting
confidence: 81%
“…Another process that can influence the zebra-stripe frequency is a fast change of the "temperature" of the hot anisotropic electrons, which can change the ratio of the upper-hybrid and electron-cyclotron frequency for the maximum of the growth rate of the upper-hybrid waves (see Fig. 7 in Benáček & Karlický 2018).…”
Section: Zebra-stripe Sources Moving In Fan Of Magnetic Field Linesmentioning
confidence: 99%
“…For ECME, a positive gradient in the EVDF is needed in the direction perpendicular to the magnetic field, , e.g. in loss-cone (Benáček & Karlický 2017), ring (Pritchett 1984; Lee, Omura & Lee 2011), horseshoe (Bingham & Cairns 2000; Melrose & Wheatland 2016), cup-like (Büchner & Kuska 1996) or shell-shaped distribution functions. The corresponding ‘inverted’ population in the velocity space led to the early authors calling this cyclotron-resonance-related mechanism a ‘maser’ mechanism.…”
Section: Introductionmentioning
confidence: 99%